Family Social Capital and Quality Management in Primary and Secondary Education - Seran, Gregorius; Ismail, Aminah binti (Metromedia, 2025)
This paper examines the relationship between family social capital manifested through parental involvement, social networks, and home learning culture and the implementation of school quality management programs. It explores how the form and quality of this capital relate to school quality initiatives, and how school strategies interact with family efforts to build a home learning culture. Using qualitative thematic synthesis of reputable literature from the past two decades, the review finds that family social capital is evidenced by emotional bonds, communication about school, structured study time, and support from extended networks. This capital shapes how families engage with school policies, translate academic goals into home routines, and communicate with educators. Successful school programs explicitly treat parents as partners, provide clear communication channels, and supply practical support for home learning. Conversely, when programs overlook variations in family social capital, quality standards tend to favor students from families with strong networks and higher education, potentially exacerbating achievement gaps. The study concludes that effective educational quality management requires recognizing families as holders of critical social resources and developing cooperative mechanisms that bridge professional school knowledge with families' daily experiences in supporting learning.